Euglycemic Diabetic Ketoacidosis Presenting as Chest Pain and Vomiting in a Patient taking SGLT-2 inhibitor (Bangladesh Critical Care Journal, 2024)
Empagliflozin-induced Euglycemic Diabetic Ketoacidosis (EDKA) is a life-threatening metabolic emergency of Diabetes Mellitus. It is characterized by metabolic acidosis (i.e., pH